2007
DOI: 10.1007/s11207-007-9011-9
|View full text |Cite
|
Sign up to set email alerts
|

Damped Oscillations of Coronal Loops

Abstract: A mechanism of damped oscillations of a coronal loop is investigated. The loop is treated as a thin toroidal flux rope with two stationary photospheric footpoints, carrying both toroidal and poloidal currents. The forces and the flux-rope dynamics are described within the framework of ideal magnetohydrodynamics (MHD). The main features of the theory are the following: i) Oscillatory motions are determined by the Lorentz force that acts on curved current-carrying plasma structures and ii) damping is caused by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Plasmas 24, 090501 (2017) quasi-stationary, occasionally buffeted by nearby eruptions causing characteristic damped oscillations. [176][177][178][179][180][181] Individual loops can show activities such as rapid variation in brightness associated with oscillations, which may be in both vertical and horizontal directions.…”
Section: -11 James Chenmentioning
confidence: 99%
“…Plasmas 24, 090501 (2017) quasi-stationary, occasionally buffeted by nearby eruptions causing characteristic damped oscillations. [176][177][178][179][180][181] Individual loops can show activities such as rapid variation in brightness associated with oscillations, which may be in both vertical and horizontal directions.…”
Section: -11 James Chenmentioning
confidence: 99%
“…The dashed thick curve shows the empirical best fitting exponentially decaying harmonic curve determined in Nakariakov et al (1999). of the corona. For example, recently, Chen & Schuck (2007) has suggested that the decay of vertically polarised kink oscillations of coronal loops could be attributed to aerodynamic drag with zero viscosity and resistivity, which provides the momentum coupling between the oscillating loop and the ambient coronal plasma. It is reasonable to expect both that a coronal loop embedded in the vertical flow should experience a periodic horizontal force due to vortex shedding, at least in the case where the external magnetic field is parallel to the plane of the loop, hence the axis of the generated vorticity, and that this force can be in resonance with natural kink oscillations of the loop.…”
Section: Phenomenon Of Vortex Sheddingmentioning
confidence: 99%
“…More recently, the same approach has been applied by Toriumi & Yokoyama (2011) to study the emergence of fluxtubes from the photosphere, by Haerendel & Berger (2011) to study the downflows in quiescent prominences, and by Chen & Schuck (2007) to study the damping of loop oscillations in the corona. Moreover, over the last few decades many authors applied the concept of a magnetic drag force to study the interplanetary propagation of solar eruptions (or coronal mass ejections -CMEs); CMEs can propagate in the intermediate corona (which extends from 1.5 to 5 solar radii) at velocities of up to 2500 km s −1 (Vourlidas et al 2002;Gopalswamy 2004), while at 1 AU velocities tend to be closer to that of the solar wind (SW; Gopalswamy 2007), around 500-800 km s −1 .…”
Section: Introductionmentioning
confidence: 99%